Hubungan Pola Konsumsi Karbohidrat Sederhana dan Karbohidrat Kompleks Dengan Kadar HbA1c Pada Penderita Diabetes Mellitus Tipe 2 Di Wilayah Kerja Puskesmas Kedawung 1 Kabupaten Sragen - Puji hastuti puji hastuti (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Background : Prevalence of Type 2 Diabetes Mellitus (DM) is epidemiologically increasing worldwide. Simple carbohidrate consumption patterns and complex carbohydrates consumption patterns are the risk factors of Type 2 DM, which can increase blood glucose levels so that it will affect DM Type 2 control through HbA1c examination. This study aimed to determine the relationship between simple carbohydrate consumption pattern and complex carbohydrates with HbA1c levels . Methods : This was an observational research using cross sectional design with 40 subject, sample was selected by total sampling which conduct in April until June 2019 at Puskesmas Kedawung 1 area. This research used FFQ questionnaire as research instrument. HbA1c levels examined using spectrophotometer. Chi square was used as statistic analysis. Results : The statistical test results suggested that there was correlation between simple carbohydrate consumption patterns and HbA1c levels (p=0,000) and also there was correlation between complex carbohydrate consumption patterns and HbA1c levels . Conclusion : There was correlation between pattern simple carbohydrate consumption and complex carbohydrate consumption with HbA1c levels. Keywords : Diabetes Mellitus, Pattern consumption , carbohydrates , HbA1c levels